2009
DOI: 10.1080/08957340902754577
|View full text |Cite
|
Sign up to set email alerts
|

A Note on Presenting What Predictive Validity Numbers Mean

Abstract: Descriptions of validity results based solely on correlation coefficients or percent of the variance accounted for are not merely difficult to interpret, they are likely to be misinterpreted. Predictors that apparently account for a small percent of the variance may actually be highly important from a practical perspective. This study combined two existing data sets to demonstrate alternative methods of showing the value of the Graduate Record Examination General Test (GRE) as an indicator of first-year gradua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 9 publications
0
18
1
Order By: Relevance
“…The uncorrected correlation values between PCAT composite scores and first-year pharmacy GPAs shown in Table 2 compare favorably with those from a study that found similar uncorrected correlation values of about 0.30 between the Graduate Record Examination (GRE) general test and first-year graduate school GPAs, and to the 90% credibility interval of 0.32-0.68 determined for PCAT total in a meta-analysis of PCAT predictive validity studies. 1,6 However, these correlations are somewhat lower than those found in a previous study conducted by the publisher of the PCAT. 7 The higher mean PCAT scores, entering GPAs, and first-year pharmacy GPAs found in the current study may reflect higher admission standards, which would result in greater range restriction and somewhat lower correlations between entering variables and first-year GPAs.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…The uncorrected correlation values between PCAT composite scores and first-year pharmacy GPAs shown in Table 2 compare favorably with those from a study that found similar uncorrected correlation values of about 0.30 between the Graduate Record Examination (GRE) general test and first-year graduate school GPAs, and to the 90% credibility interval of 0.32-0.68 determined for PCAT total in a meta-analysis of PCAT predictive validity studies. 1,6 However, these correlations are somewhat lower than those found in a previous study conducted by the publisher of the PCAT. 7 The higher mean PCAT scores, entering GPAs, and first-year pharmacy GPAs found in the current study may reflect higher admission standards, which would result in greater range restriction and somewhat lower correlations between entering variables and first-year GPAs.…”
Section: Discussioncontrasting
confidence: 51%
“…6 Table 3 shows that the addition of PCAT scores to entering GPAs represents an incremental variance of 6%. While accurate, such conventional portrayals of incremental variance may appear misleadingly small and may not clearly suggest the value that PCAT scores add to entering GPAs.…”
Section: Multiple Regression Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Bridgeman, Burton, and Cline () suggested a valuable comparison of outcomes for top versus bottom GRE score quartiles of enrolled students to illustrate predictive validity. Limitations of this approach include omitting part of the score distribution, communicating validity for enrolled students rather than the applicant pool, and conveying only univariate information when decision makers might simultaneously use more than one predictor.…”
Section: Quartile Comparisonsmentioning
confidence: 99%
“…In addition to studies of methods for estimating the economic impact of organizational interventions, there has been a lively literature dealing with the credibility and meaning of these estimates to users (e.g., Bridgeman, Burton and Cline, 2009;Hazer and Highhouse, 1997;Whyte and Latham, 1997). One conclusion from this literature is that simply presenting financial projections to end users without a clear and compelling description of how interventions in organizations actually deliver these benefits tends to undermine the credibility of projections of financial benefits.…”
Section: Introductionmentioning
confidence: 99%